Sunday

December 21, 2014

December 21, 2014

Posted by **zinnia** on Sunday, August 5, 2007 at 11:27am.

Rewrite the equation as

(x/3)^2 - (y/9)^2 = 1

When both x and y are very large in absolute value, the "1" on the right is negligible in comparison, so y/9 approaches +/- x/3

The asymptotes are therefore

y = 3x and y = -3x.

**Answer this Question**

**Related Questions**

Algebra - HELP! I am not sure how I would even start this problem or solve it. A...

Math - Given the hyperbola[(x+3)^2/4]-[(y-1)^2/9]=1,find the equations of the ...

Algebra - Given the hyperbola (x2/4) – (y2/9) = 1, find the equations for its ...

math 30 conics - Hi i was given the equation (y-2)^2 - x^2/4 =1. I need to find ...

algebra - 1)What is the 4x^2=y^2+8y+32 answer= either hyperbola or parabola 2)...

Pre-calculus-ck answers - Identify the graph of the equation 4x^2-25y^2=100. ...

math - how do I find the asymptotes of the hyperbola in the following equation...

Precalc - Write the equation of the hyperbola whose center is at the origin and ...

math-algebra - 10. What are the equations of the asymptotes for the hyperbola...

math-algebra - 10. What are the equations of the asymptotes for the hyperbola?: ...